2017
DOI: 10.1016/j.jccase.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable case of late-onset biatrial bacterial endocarditis of the Gore HELEX septal occluder

Abstract: Metaanalyses of trials comparing medical treatment versus surgical closure of patent foramen ovale (PFO) have shown that percutaneous closure is more effective for preventing recurrent thromboembolic events [1]. Common complications of any occluder device include device thrombus formation, transient ischemic attack, pericardial tamponade, device dislocation, arrhythmias, and endocarditis [1]. In this article, we take a closer look at endocarditis post-device implant. It is established that up to 6 months post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…After extensive literature review, we found 23 reported cases of IE on ASD closure devices (Table 1 , Ref. [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]).…”
Section: Closure Devices and Shuntsmentioning
confidence: 99%
See 1 more Smart Citation
“…After extensive literature review, we found 23 reported cases of IE on ASD closure devices (Table 1 , Ref. [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]).…”
Section: Closure Devices and Shuntsmentioning
confidence: 99%
“…Median age of subjects with device IE was 37 years and most developed endocarditis beyond 6 months of device implantation (17/23, 78%). Fever was the most common presenting symptom (n = 22/23, 95%), and other presentations included stroke/other site embolism (n = 10/23, 42%, pulmonary embolism in one case [ 56 ]), septic shock (n = 2/23, 8%), immunologic phenomena (n = 3/23, 13%), and acute meningitis (n = 1/23, 4%).…”
Section: Closure Devices and Shuntsmentioning
confidence: 99%